About metaphysics - Dávila Morey, Dante (2017)
In our times, metaphysics has become a study of dubious nature to such an extent that it has been tried to be eliminated from philosophy. But what are we talking about when we refer to metaphysics? What it has been like and what it is for having experienced such a strange destiny? In the following, three theses will be discussed: the first, metaphysics is its problems; the second, metaphysics is its history; and the third, metaphysics is its possibilities.